Article Review: Glimepiride Solubility Enhancement Strategy as Diabetes Treatment Therapy - Fiftianingrum, Valentina; Sopyan, Iyan; Gozali, Dolih (Jurnal Locus Penelitian dan Pengabdian, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by high blood glucose levels due to impaired insulin secretion. The prevalence of diabetes in Indonesia always increases every year. Glimepiride is a type 2 antidiabetic drug of the sulfonylurea class that works by stimulating insulin secretion of pancreatic beta cells. Glimepiride is given through the oral route of administration and is widely used because it has a longer half-life and can be used as treatment monotherapy. Glimepiride itself has physicochemical properties that can penetrate the stratum corneum with a dose of less than 10 mg, a molecular weight of 490.62 g/mol, a melting point of 207°C, and a lipophilicity value (LogP) of 3.5. However, oral glimepiride in therapy has bioavailability problems due to its poor solubility in the gastrointestinal tract. It has very low solubility values at acidic and neutral pH of approximately less than 0.004 mg/mL (BCS 2). Due to the low aqueous solubility of glimepiride is a major challenge in drug formulation development. This low solubility has an impact on its bioavailability, which is not optimal, thus reducing its therapeutics. Various efforts were made in order to increase the solubility of glimepiride, including the use of formulation techniques such as the preparation of solid dispersion systems, the formation of inclusion complexes, as well as the utilization of nanoparticle technologies such as nanosuspensions, nanoemulgels, and nanoemulsions. In addition, chemical modification approaches and various others are used to improve the solubility of glimepiride. Recent studies have shown that the combination of the latest formulation technologies with suitable carrier materials can significantly improve its solubility and stability, thereby enhancing the therapeutic effectiveness of glimepiride in the management of type 2 diabetes. Thus, innovations in glimepiride formulation are expected to provide better therapeutic solutions for patients with type 2 diabetes.